1999
DOI: 10.1164/ajrccm.160.5.9806004
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Diaphragmatic Function Induced by Acute Necrotizing Pancreatitis in a Rodent Model

Abstract: Some of the common complications of acute necrotizing pancreatitis also involve pulmonary complications. These manifestations are often associated with a cephalad diaphragmatic shift. We hypothized that diaphragmatic function might be directly compromised by the acute abdominal process. This hypothesis was tested on an acute necrotizing pancreatitis (ANP) rat model. We assessed the diaphragm and peripheral (Extensor Digitorum Longus and Soleus) muscle properties in vitro using strips in control (C) and ANP ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Atelectasis, alveolar flooding [29], alteration in diaphragmatic function [30] and systemic inflammatory response syndrome [31] contribute to the development of ARF. The use of NPPV with pressure support ventilation and PEEP allows for increased lung volume with reexpansion of atelectasis [32], decreased work of breathing [14, 33] and pulmonary extravascular water [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atelectasis, alveolar flooding [29], alteration in diaphragmatic function [30] and systemic inflammatory response syndrome [31] contribute to the development of ARF. The use of NPPV with pressure support ventilation and PEEP allows for increased lung volume with reexpansion of atelectasis [32], decreased work of breathing [14, 33] and pulmonary extravascular water [34].…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in diaphragmatic function in AP could also be a possible mechanism responsible for its cephalad displacement and occurrence of atelectasis. In experimental studies, Matuszczak et al [30] reported that an edematous pancreatitis rat model induced marked alteration in diaphragmatic function, whereas there was no change in peripheral muscle contractility. …”
Section: Discussionmentioning
confidence: 99%
“…This is also probably true in the case of abdominal disorders. Diaphragmatic histology was normal and muscular levels of myeloperoxidase, a marker of neutrophil infiltration, did not increase in either the muscle of the Pseudomonas-infected animals (2) or in animals with pancreatitis and peritonitis (3,5), thus excluding direct extension of the infectious/inflammatory process to the muscle. Anatomical proximity to the infectious site could, however, be responsible for direct exposure of the diaphragm to bacteria and/or inflammatory mediators synthesized in the infected organ via direct lymphatic spread (8).…”
Section: Placing Basic Research In Clinical Perspectivementioning
confidence: 93%
“…Damaged tissue releases chemotactic factors that accumulate neutrophils. Gathered neutrophils blocks the lumen and increase the release of enzymes, free oxygen radicals, and other inflammatory mediators such as protease and elastase (22). All these events incessantly trigger each other, leading to a vicious cycle.…”
Section: Hançerli Et Al Efficacy Of Tocilizumab In Pancreatitis Modelmentioning
confidence: 99%